Penguatan Moderasi Beragama dalam al-Quran: Sebuah Kajian Tematik - Ainur Rosyidah (Matan : Journal of Islam and Muslim Society, 2021)
Strengthening religious moderation is very important to be discussed again because the potential for social conflict among the community is exist. In this case, no matter how small the problems that exist in society, we must remain vigilant given the potential for violent conflict, which is often linked to the religion. Therefore, it is very important to study the verses of the Quran related to strengthening religious moderation, especially in qv. al-Baqarah/2: 143, qv. al-Rum/30: 30, qv. al-Maidah/5: 8, and qv. Ali Imran/3: 110. This study aims to explore strengthening religious moderation in the Quran. This research is a literature research with a thematic interpretation study approach which is presented descriptively. The results showed that qv. al-Baqarah/2: 143 is a basic guide for human behavior that must be balanced or moderate. Another guide to moderation is stated in the qv. al-Rum/30: 30, qv. al-Maidah/5: 8, and qv. Ali Imran/3:110 to always side with the truth, uphold justice, invite goodness, and leave badness.